2022
DOI: 10.1155/2022/6223404
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of Table Eggs in Moroccan Formal and Informal Sector

Abstract: Eggs constitute an important part of the Moroccan diet. However, contaminated eggs can cause a serious public health problem if consumed undercooked, uncooked, or used in unpasteurized egg foodstuffs. This study was carried out to evaluate the microbial contents of eggs according to their sales sector in Morocco. For that, a total of 1770 eggs were collected from January to September 2021 from formal markets (refrigerated eggs from large shopping centers) and informal markets (eggs at ambient temperature from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…aureus contamination is also found in fresh eggs and produce processed over 10 years. The data in Table 2 [22][23][24][25][26][27][28][29][30][31][32][33][34][35] show that bacteria were found on farms, traditional markets, supermarkets, and shops selling material food. The number of S. aureus found in shell eggs is generally higher than in white and yolk eggs.…”
Section: S Aureus Contamination In Eggs and Egg Products In Indonesiamentioning
confidence: 99%
“…aureus contamination is also found in fresh eggs and produce processed over 10 years. The data in Table 2 [22][23][24][25][26][27][28][29][30][31][32][33][34][35] show that bacteria were found on farms, traditional markets, supermarkets, and shops selling material food. The number of S. aureus found in shell eggs is generally higher than in white and yolk eggs.…”
Section: S Aureus Contamination In Eggs and Egg Products In Indonesiamentioning
confidence: 99%
“…Many studies have isolated Salmonella spp. and E. coli from eggs (Adesiyun et al, 2005;Stepien, 2010;El ftouhy et al, 2022), and several egg-borne outbreaks of salmonellosis have been reported (Guerra-Centeno et al, 2020), considering eggs a possible vehicle for resistant bacteria and genes.…”
Section: Introductionmentioning
confidence: 99%